PENGARUH PENGGUNAAN MEDIA ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA PADA MATERI SIKLUS AIR KELAS V SDN TAMBAAN 1 - Rahmawati Solikin; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Assembler Edu media on student learning outcomes in the water cycle material of class V SDN Tambaan 1. This study uses a quantitative research type of experimental method with a Pre-Experimental Design design in the form of One-Group Pretest-Posttest Design. The population in this study were all students of class V UPTD SDN Tambaan 1. Sampling used a saturated sampling technique. The research sample consisted of 26 students. Data were collected using observation, tests, and questionnaires. The prerequisite test used was a normality test with the Shapiro Wilk technique, which was then tested with a paired sample t-test to test the hypothesis. The results of the hypothesis test show that the Sig. (2-tailed) value is 0.00 <0.05 so it can be said that HO is rejected and it can be concluded that there is a significant influence on the use of Assemblr Edu media on the water cycle material on the learning outcomes of class V students.